2001
DOI: 10.1021/jp004308o
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics Study of the OH + O2 Branching Atmospheric Reaction. 2. Influence of Reactants Internal Energy in HO2 and O3 Formation

Abstract: The effect of reactants vibrational and rotational excitation on products (HO 2 + O and O 3 + H) formation is investigated for the title reaction by using the quasiclassical trajectory method and the realistic double manybody expansion (DMBE) potential energy surface for ground-state HO 3. It is shown that it can be a potential source of ozone in the upper atmosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
2
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 39 publications
4
47
2
1
Order By: Relevance
“…Note that the combination OH(V′ ) 0) + O 2 (V′′ ) 16) (see ref 29) corresponds roughly to the "effective" threshold energy (the true threshold energy occurs for V′′ ≈ 13) for HO 2 formation. It lies approximately 66 kcal mol -1 above the zero-point energy of the reactants channel (see ref 30) and 14 kcal mol -1 over the HO 2 + O products. However, the bold part of the reactive processes (eq 5 to eq 8) occurs roughly at total energies of 128 kcal mol -1 , and hence we focused in this work on such energy regimes.…”
Section: Computational Detailsmentioning
confidence: 90%
See 1 more Smart Citation
“…Note that the combination OH(V′ ) 0) + O 2 (V′′ ) 16) (see ref 29) corresponds roughly to the "effective" threshold energy (the true threshold energy occurs for V′′ ≈ 13) for HO 2 formation. It lies approximately 66 kcal mol -1 above the zero-point energy of the reactants channel (see ref 30) and 14 kcal mol -1 over the HO 2 + O products. However, the bold part of the reactive processes (eq 5 to eq 8) occurs roughly at total energies of 128 kcal mol -1 , and hence we focused in this work on such energy regimes.…”
Section: Computational Detailsmentioning
confidence: 90%
“…More recently, we have suggested that ozone could be produced through the reaction [29][30][31] in conjunction with the three-body recombination of the atomic oxygen produced by other channels of the branching reaction 5, namely Moreover, further atmospheric ozone sources have been suggested in our Group involving vibrationally excited O 2 (V′, j′) 6,7,8 or HO 2 (W) 32 instead of OH(V′) in eq 5 [and, correspondingly, in eq 6 to eq 8]; W stands for the three vibrational normal modes of HO 2 . In addition, it has been shown that the traditional O x and HO x ozone depletion cycles could be reformulated to act as ozone sources.…”
Section: Introductionmentioning
confidence: 99%
“…We emphasize that only collisions of OH(V′) with vibrationally cold O 2 are considered, leaving aside the reactive processes which have also been a subject of previous studies. 23,27,28 For consistency, all …”
Section: Trajectory Simulation Of Steady-state Distributionsmentioning
confidence: 99%
“…Net: 3O 2 + 4hν f 2O 3 (26) σ r ) CE tr -n + BE tr 2 exp(-mE tr ) (27) with the translational energy E tr in kcal mol -1 the cross section is in a 0 2 . From eq 27, the corresponding specific rate constant can be calculated analytically 43 as a function of temperature yielding k ) 1.7 × 10 -13 cm 3 s -1 at T ) 255 K. This is roughly one-half of the rotationally thermalized value reported above, although the 68% error bars in the reactive cross sections are appreciable despite the fact that 3000 trajectories have been run per translational energy.…”
Section: The Reaction Ho 2 (V) + O 2 (V′′)mentioning
confidence: 99%
“…This implies that the reactions 1-3 are feasible over the complete range of translational energies. Note that, for the internal energy combination (20,51) …”
Section: Potential Energy Surfacementioning
confidence: 99%